If x = 6a + 86 + 9c ; y = 2b – 3a – 6c and z = c – b + 3a ; find x + y + z

0 votes
1 view
asked May 16 in Class VIII Maths by muskan15 (-2,329 points)

If x = 6a + 86 + 9c ; y = 2b – 3a – 6c and z = c – b + 3a ; find
(i) x + y + z
(ii) x – y + z
(iii) 2x – y – 3z
(iv) 3y – 2z – 5x

Please log in or register to answer this question.

1 Answer

0 votes
answered May 16 by priya12 (-11,279 points)

(ii) x – y + z

 = (6a + 8b + 9c) – (2b – 3a – 6c) + (c – b + 3a)

= 6a + 8b + 9c – 2b + 3a + 6c + c – b + 3a

= 6a + 3a + 3a + 8b – 2b – b + 9c + 6c + c

= 12a + 5b + 16c

(iii) 2x – y – 3z

= 2(6a + 8b + 9c) – (2b – 3a – 6c) – 3(c – b + 3a)

= 12a + 3a – 9a + 16b + 3b – 2b + 18c + 6c – 3c

= 6a + 17b + 21c

(iv) 3y – 2z – 5x

= 3(2b – 3a – 6c) – 2(c – b + 3a) – 5(6a + 8b + 9c)

= 6b – 9a – 18c – 2c + 2b – 6a – 30a – 40b – 45c

= -45a – 32b – 65c

Related questions

...